Advanced technology conversion specifics in sports - Mukhaev, S. V.; Semenov, L. A. (Theory and Practice of Physical Culture, 2017)
The study provides theoretical grounds for the principle of the advanced technology conversion in sports, with the conversion process designed on the vertical (from elite sports to youth sports and further to sportizated physical education) and horizontal bases (from one sport discipline to others). The key conversion process rules and frame process model are offered.